Corporate Social Responsibility Reporting in China - Shin, Kwang-Yong.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
The CSR report has become a very important tool which can help corporations to set up strategies and build their core competencies. This book presents a range of cases from different industries. Based on the analysis of the enterprise survival environment, it points out the necessity and significance of CSR. The book analyzes the current situation and development trend of CSR in China, as well as its international developing trend. By analyzing the management framework and formulation process of the CSR report, this book provides businesses with guiding principles for preparing the CSR report.
Corporate Social Responsibility -- CSR Management -- Overview of CSR Report -- The Current Situation and Development Trend of Global CSR -- Current Situation and Development Trend of CSR Report in China -- Management Framework for CSR Report -- The Reference Standard of CSR Report -- The Contents and Structure of CSR Report -- The Compilation and Testing of CSR Report -- E-CSR Report Management -- Release and Marketing of CSR Report -- Cases of CSR Reports in China.
Keywords: Economics; Economics/Management Science; Non-Profit Enterprises/Corporate Social Responsibility; Organizational Studies, Economic Sociology